Effect of the Fermentation Time of Purple Sweet Potato (Ipomea batatas L) Synbiotic Yoghurt with Probiotic Starter on Product Quality and Antioxidant Activity - Setiawan, Azzahra Laili Tivalia Putri; Agustini, Rudiana (Jurnal Pijar Mipa, 2024)
Purple sweet potato (Ipomea batatas L) has the potential as a fermentation medium because it has a high carbohydrate content of around 20.1%. The combination of purple sweet potato extract, skimmed milk, and probiotic starter is expected to be a synbiotic yogurt that can help the digestive system. This study aims to determine the effect of long-term fermentation of purple sweet potato synbiotic yogurt with probiotic starter culture on product quality and antioxidant activity. The observed quality was chemical, microbiological, and organoleptic, with variations in fermentation time of 0, 4, 8, and 12 hours. The study's results showed a long-term effect of the fermentation of purple sweet potato synbiotic yogurt with probiotic starter culture on the quality of yogurt. The variation of 0-hour fermentation time did not meet the pH chemical quality standard with a value of 5.16. Still, it met the TAT chemical quality standard with a value of 0.513%, while the variation of fermentation time of 4-12 hours met the pH quality standard with a value of 3.88-4.33 and a TAT of 1.268-1.967%. In the quality of microbiology, there was a total increase in BAL, which was 46.2×107 - 90.61×107. The best organoleptic quality of color, taste, and aroma was obtained in the 8-hour fermentation variation, while the best texture organoleptic quality was obtained in the 12-hour fermentation variation. The best antioxidant activity was received at 12 hours of fermentation with an IC50 value of 62.727 ppm. From this study, it can be concluded that the best yogurt results are obtained with a fermentation time of 12 hours.